Succession with the Foreign Element of a Share in a Limited Liability Company Registered in Ukraine - Dikovska, Iryna (Teisė, 2022)
The paper aims at the revealing of the possible manifestations of foreign element in a succession of a share in a limited liability company registered in Ukraine; distinguishing the issues which should be governed by lex societatis and lex successionis; determining of lex societatis and lex successionis as well as international competence of notaries and international jurisdiction of courts in the matters of succession of share in a limited liability company registered in Ukraine. To achieve this aim the paper analyses some bilateral international treaties of Ukraine on legal assistance and the Law of Ukraine On Private International Law. The solution of the issues which have not been solved in Ukrainian law was offered taking into consideration the solutions of the Regulation (EU) No 650/2012 of the European Parliament and of the Council of 4 July 2012 on jurisdiction, applicable law, recognition and enforcement of decisions and acceptance and enforcement of authentic instruments in matters of succession and on the creation of a European Certificate of Succession, as well as the law of Germany, France, the Netherlands and Switzerland.
Keywords: international succession; law applicable to the succession of a share in the company; international jurisdiction in succession matters; Law of Ukraine On Private International Law; international treaties on legal assistance on civil matters; EU Succession Regulation; the rights arising out of a share in company